A comprehensive review of rock dust for soil remineralization in sustainable agriculture and preliminary assessment of nutrient values in micronized porous basalt rock from Nghe-An province, Vietnam - Nguyen Khanh Son; Nguyen Hoang Thien Khoi; Nguyen Ngoc Tri Huynh; Nguyen Vinh Phuoc (Vietnam Journal of Science and Technology, 2024)
This review delves into the utilization of rock powder as a mineral-derived fertilizer to support soil remineralization in the context of sustainable agriculture. Soil remineralization has emerged as a key strategy for ensuring long-term soil fertility and reducing the dependency on synthetic fertilizers. This review critically assesses the methodological approaches applied in various studies, taking into account factors such as local rock mineralogy, soil conditions, crop types, and nutrient uptake by plants. The review covers a range of methods, including nutrient value analysis, assessment of nutrient release rates, crop cultivation experiments in both laboratory and field settings, and the resulting implications for soil remineralization. Additionally, we present findings from a preliminary study focusing on the nutrient content of basalt rock from Nghe-An Province, Vietnam. This experimental investigation is centered on the assessment of nutrient values in a specific porous basalt material, which has been processed into micro-nanometer particles using a high-energy ball mill, thereby enhancing nutrient release efficiency. The study employs a range of analytical techniques, including XRD, XRF, SEM/EDS, and ICP-MS, to quantify macro- and micro-nutrient compositions. While the basalt rock samples may exhibit limitations in providing macronutrients (such as K) compared to commercial azomite rock, they offer distinct advantages in furnishing secondary macronutrients (like Ca). This comprehensive analysis provides insights into the potential use of micronized basalt rock for soil remineralization.